Pseudoaneurysm of anomalous cystic artery due to calculous cholecystitis - Kulkarni, Varsha (BMJ Case Rep, 2014)
Pseudoaneurysm of the cystic artery is a rare cause of haemobilia resulting from either an inflammatory process in the abdomen or abdominal trauma. We report a case of a patient with chronic calculous cholecystitis associated with a pseudoaneurysm arising from an anomalous cystic artery who presented with haemobilia. The patient was managed successfully with multimodality treatment that included angioembolisation of the pseudoaneurysm and stenting of the common bile duct to relieve jaundice followed by elective open cholecystectomy.